Sociodemographic and clinical factors, visit expectations and driving factors for emergency department attendance for uncomplicated upper respiratory tract infection. Issue 6 (23rd December 2021) - Chow, Angela; Keng, Bryan; Guo, Huiling; Aung, Aung Hein; Huang, Zhilian; Weng, Yanyi; Ang, Hou
Abstract : Background: Upper respiratory tract infections (URTIs) account for substantial non-urgent ED attendances. Hence, we explored the reasons for such attendances using a mixed-methods approach. Methods: We interviewed adult patients with URTI who visited the second busiest adult ED in Singapore from June 2016 to November 2018 on their expectations and reasons for attendance. A structured questionnaire, with one open-ended question was used. Using the Andersen's Behavioural Model for Healthcare Utilisation, the topmost reasons for ED attendances were categorised into (1) contextual predisposing factors (referral by primary care physician, family, friends or coworkers), (2) contextual enabling factors (convenience, accessibility, employment requirements), (3) individual enablers (personal preference and trust in hospital-perceived care quality and efficiency) and (4) individual needs (perceived illness severity and non-improvement). Multivariable multinomial logistic regression was used to assess associations between sociodemographic and clinical factors, patient expectations for ED visits and the drivers for ED attendance. Results: There were 717 patients in the cohort. The mean age of participants was 40.5 (SD 14.7) years, 61.2% were males, 66.5% without comorbidities and 40.7% were tertiary educated. Half had sought prior medical consultation (52.4%) and expected laboratory tests (55.7%) and radiological investigations (46.9%). Individual needs (32.8%) and enablers (25.1%) were the main drivers for ED attendance. Compared with ED attendances due to contextual enabling factors, attendances due to other drivers were more likely to be aged ≥45 years, had prior medical consultation and expected radiological investigations. Having a pre-existing medical condition (adjusted OR (aOR) 1.78, 95% CI 1.05 to 3.04) and an expectation for laboratory tests (aOR 1.64, 95% CI 1.01 to 2.64) were associated with individual needs while being non-tertiary educated (aOR 2.04, 95% CI 1.22 to 3.45) and having pre-existing comorbidities (aOR 1.79, 95% CI 1.04 to 3.10) were associated with individual enablers. Conclusions: Meeting individual needs of perceived illness severity or non-improvement was the topmost driver of ED visits for URTI, while contextual enabling factors such as convenience was the lowest. Patients' sociodemographic and clinical factors and visit expectations influence their motivations for ED attendances. Addressing these factors and expectations can alleviate the overutilisation of ED services.